Ethanolic extract of Mimosa caesalpiniifolia leaves: Chemical characterization and cytotoxic effect on human breast cancer MCF-7 cell line - Silva, M. J. D. [UNESP]; Carvalho, A. J. S.; Rocha, C. Q. [UNESP]; Vilegas, Wagner [UNESP]; Silva, M. A.; Gouvea, C. M. C. P. (Elsevier B.V., 2014)
Mimosa caesalpiniifolia popularly known as sabia or sansao-do-campo is a Brazilian Northeast native perennial tree used for several purposes and in traditional medicine. The aim of the present work was to determine some of the constituents and evaluate the cytotoxic activity of the ethanolic extract of M. caesalpiniifolia leaves (EEM) to MCF-7 cells, a human breast adenocarcinoma cell-line. EEM presented 651.90 +/- 630 mg/g total phenols and 170.11 +/- 1.20 mg/g flavonoids, namely catechin. EEM and cyclophosphamide (cytotoxic agent) treatment for 24 and 48 h decreased the MCF-7 cells protein content, as compared to control cells. Morphological analysis, after hematoxylin-eosin staining of cells, showed changes such as cell rounding-up, shrinkage, nuclear condensation and significantly (p < 0.01) reduction of cell and colony diameters, that indicates the EEM cytotoxic effect to MCF-7 cells. EEM treatment also induced cell death, with a maximum effect at 320.0 mu g/mL, and its mechanism of action seems to include the induction of apoptosis, as DNA fragmentation in a ladder-pattern was obtained from the genomic DNA analysis. Our data support a positive role of the EEM as a chemopreventive agent and a good candidate for an antineoplastic drug development. (C) 2014 SAAB. Published by Elsevier B.V. All rights reserved.
Keywords: Anticancer; Cell death; Cell morphology; Plant extract; Sable